Properties of composite vacuum-arc coatings of the TiN-Ti/TiON structure - Andreev, А.; Kostyk, G.; Sysoiev, Iu.; Minaiev, N. (Вопросы атомной науки и техники, 2018)
Complex investigation of composite coatings with the structure TiN-Ti/TiON is performed in work. It was identified that morphology of the surface of the multilayer coating TiN-Ti provides high adhesion between it and next layer of titanium nitride oxide; three phases in the samples covered with TiN-Ti/TiОN and TiОN is revealed TiN with the cubic grating of NaCl type, α-Ti and amorphous titanium oxide TiO₂; at titanium layer thickness in multi-layer system TiN/Ti less than 100 nm sufficiently high mechanical properties are obtained (hardness more than 25 GPa at a plasticity index Н/E* = 0.11…0.12) that at known increase of crack resistance of such coatings make them promising for conditions of high alternating loads; after application of titanium oxynitride of ~ 1 μm thickness on the multilayer coating TiN/Ti of 6 μm (titanium layers – 30 nm, layers TiN – 300 nm) the hardness of the composite coating increases and reachs 27…28 GPa; the first cracks in scrubbing in the coating appear at the load 3.86 N the coefficient of friction does not exceed 0.1; the TiN-Ti/TiON coating has a significantly higher wear resistance than the TiN-Ti coating and in an order greater than the 12Х18Н9Т steel; TiN-Ti/TiON coated samples have high corrosion resistance in a 2% NaCl solution, due to the very low rate of their corrosion, that is a consequence of the structure of the TiN-Ti multilayer coating that has no columnar structure. Виконано комплексне дослідження властивостей композиційних покриттів структури TiN-Ti/TiON. Встановлено: морфологія поверхні багатошарового покриття TiN-Ti сприяє забезпеченню високої адгезії між ним та подальшим шаром оксинітриду титану; у зразках, вкритих TiN-Ti/TiОN і TiОN, виявляється присутність трех фаз: TiN з кубічною решіткою типу NaCl, α-Ti та аморфноподібний окисел титану TiO₂; при товщині шару титану в багатошаровій системі TiN-Ti менше 100 нм досягаються досить високі механічні властивості (твердість більше 25 ГПа при індексі пластичності Н/E* = 0,11...0,12); після нанесення оксинитрида титану товщиною ~ 1 мкм на багатошарове покриття TiN-Ti товщиною 6 мкм (шари титану – 30 нм, шари TiN – 300 нм) твердість композиційного покриття зростає і становить 27...28 ГПа; перші тріщини при скрайбуванні в покритті з'являються при навантаженні 3,86 Н, при цьому коефіцієнт тертя не перевищує 0,1; покриття TiN-Ti/TiON має значно більш високу зносостійкість, ніж покриття TiN-Ti, і на порядок більшу, ніж сталь 12Х18Н9Т; зразки з покриттям TiN-Ti/TiON мають високу корозійну стійкість в розчині 2% NaCl, яка спричинена дуже низькою швидкістю їх корозії, що представляється наслідком структури багатошаро-вого покриття TiN-Ti, яка не має стовбчастої будови. Выполнено комплексное исследование свойств композиционных покрытий структуры TiN-Ti/TiON. Установлено: морфология поверхности многослойного покрытия TiN-Ti способствует обеспечению высокой адгезии между ним и последующим слоем оксинитрида титана; в образцах, покрытых TiN-Ti/TiОN и TiОN, выявляется присутствие трех фаз: TiN с кубической решеткой типа NaCl, α-Ti и аморфноподобный окисел титана TiO₂; при толщине слоя титана в многослойной системе TiN/Ti менее 100 нм достигаются достаточно высокие механические свойства (твердость более 25 ГПа при индексе пластичности Н/E* = 0,11…0,12), что при известном росте трещиностойкости таких покрытий делает их перспективными для использования в условиях действия высокой знакопеременной нагрузки; после нанесения оксинитрида титана толщиной ~ 1 мкм на многослойное покрытие TiN/Ti толщиной 6 мкм (слои титана – 30 нм, слои TiN – 300 нм) твердость композиционного покрытия возрастает и составляет 27…28 ГПа; первые трещины при скрайбировании в покрытии появляются при нагрузке 3,86 Н, при этом коэффициент трения не превышает 0,1; покрытие TiN-Ti/TiON обладает значительно более высокой износостойкостью, чем покрытие TiN-Ti, и на порядок большей, чем сталь 12Х18Н9Т; образцы с покрытием TiN-Ti/TiON обладают высокой коррозионной стойкостью в растворе 2% NaCl, обусловленной очень низкой скоростью их коррозии, что представляется следствием структуры многослойного покрытия TiN-Ti, которая не имеет столбчатого строения.